China$1 (Bs Macroeconomic Outlooks Quarterly Forecast and Analysis Report, September 2015 - Li, Wenpu; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book is a quarterly forecast and analysis report on the Chinese economy. It is published twice a year and presents ongoing results from the (3z(BChina Quarterly Macroeconomic Model (CQMM),(3y (Ba research project at the Center for Macroeconomic Research (CMR) at Xiamen University. Based on the CQMM model, the research team forecast major macroeconomic indicators for the next 8 quarters, including the rate of GDP growth, the CPI, fixed-asset investment, resident consumption and foreign trade. At the same time it focuses on simulation of current macroeconomic policies in China. In addition to helping readers understand China$1 (Bs economic trend and policy guide, this book has three main goals: to help readers understand China$1 (Bs economic performance; to forecast the main macroeconomic indicators for the next 8 quarters; and to simulate the effectiveness of macroeconomic policies.s
Preface -- Introduction -- Chapter 1 A Review of China$1 (Bs Economy in the First Half of 2015 -- Chapter 2 China$1 (Bs Macroeconomic Forecast from 2015 to 2016 -- Chapter 3 Policy Simulation: Macro Effects of Interest Rate Liberalization -- Chapter 4 Optimization of Economic Structure and China$1 (Bs Growth Potential -- Chapter 5 Conclusions and Policy Suggestions -- Appendix 1 Specification of the Production Function and Estimation -- Appendix 2 Forecast of the Potential Growth Rate -- Appendix 3 The Macroeconomic Situation and Policy of China in 2015.s
Keywords: Macroeconomics; Public finance; Economic growth; Economics; Macroeconomics/Monetary Economics//Financial Economics; Economic Growth; Public Economics; Electronic books